2005
DOI: 10.1039/b500291e
|View full text |Cite
|
Sign up to set email alerts
|

One-pot catalyst preparation: combined detemplating and Fe ion-exchange of BEA through Fenton's chemistry

Abstract: One-pot catalyst preparation Melián-Cabrera, I.; Kapteijn, F.; Moulijn, J.A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…• shifting the complexation equilibria for ion-exchange by oxidation of the organic chelates [146]; • one-pot synthesis of metal-exchanged zeolites [147];…”
Section: Can We Use Fenton Chemistry In Solid Catalyst Synthesis?mentioning
confidence: 99%
See 3 more Smart Citations
“…• shifting the complexation equilibria for ion-exchange by oxidation of the organic chelates [146]; • one-pot synthesis of metal-exchanged zeolites [147];…”
Section: Can We Use Fenton Chemistry In Solid Catalyst Synthesis?mentioning
confidence: 99%
“…We discuss here a combined process including detemplation and Fe incorporation by ion-exchange in the zeolite framework [147]. To achieve this, oxidants to decompose the organic template and Fe-cations for exchange are needed.…”
Section: Second Concept In Catalyst Design One-pot Synthesis Of Fe Zmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it is reported that the detemplation of zeolite beta could be achieved by oxidation of the template using H 2 O 2 (Melián-Cabrera et al 2005). With this approach, the original structure of the material was well preserved and no extra-framework aluminum was formed.…”
Section: Introductionmentioning
confidence: 99%